2005
DOI: 10.1128/aem.71.4.2130-2139.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubsp.paratuberculosisin the Catchment Area and Water of the River Taff in South Wales, United Kingdom, and Its Potential Relationship to Clustering of Crohn's Disease Cases in the City of Cardiff

Abstract: In South Wales, United Kingdom, a populated coastal region lies beneath hill pastures grazed by livestock in which Mycobacterium avium subsp. paratuberculosis is endemic. The Taff is a spate river running off the hills and through the principal city of Cardiff. We sampled Taff water above Cardiff twice weekly from November 2001 to November 2002. M. avium subsp. paratuberculosis was detected by IS900 PCR and culture. Thirty-one of 96 daily samples (32.3%) were IS900 PCR positive, and 12 grew M. avium subsp. par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(167 citation statements)
references
References 72 publications
6
160
0
1
Order By: Relevance
“…Mycobacterium paratuberculosis has been shown to survive in a variety of environmental conditions ranging from several weeks in barn dust samples to almost two years in river sediment (Pickup et al, 2005;Tkachuk et al, 2013). This highlights the plausible link between ruminant excretion of M.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mycobacterium paratuberculosis has been shown to survive in a variety of environmental conditions ranging from several weeks in barn dust samples to almost two years in river sediment (Pickup et al, 2005;Tkachuk et al, 2013). This highlights the plausible link between ruminant excretion of M.…”
Section: Discussionmentioning
confidence: 97%
“…Contamination of surface water, including lakes and rivers fed by runoff areas and water troughs, was investigated in seven studies that reported an overall prevalence of 12.8% culture-positive and 42.6%-90% PCR-positive samples in several countries (Table 2). M. paratuberculosis can survive for 16-20 weeks in water and 28 to more than 90 weeks in sediment, thus the aquatic environment may be a significant source for both humans and animals (Pickup et al, 2005;Whittington et al, 2005). Based on environmental inoculation experiments, slope of the land and concentration of M. paratuberculosis on the soil were strong determinants of the contamination in runoff water (Salgado et al, 2013).…”
Section: Prevalence In Watermentioning
confidence: 99%
“…Water, regardless of origin and quality, can be contaminated by mycobacteria and, under specific conditions, can jeopardise the users (Falkinham III 2003;Falkinham 2009a,b). Pickup et al (2005) reported that M. avium subsp. paratuberculosis can be present in high concentrations in the river water in the catchments area of pastures.…”
Section: Mycobacteria In Watermentioning
confidence: 99%
“…IS900 is specific for M. avium subsp. paratuberculosis and is the most widely used sequence for its detection (Pickup et al 2005(Pickup et al , 2006Whan et al 2005;Torvinen et al 2010). For detection of M. avium subsp.…”
Section: Identification Of Mycobacteriamentioning
confidence: 99%
“…The organism remains culturable in lake water microcosms for 632 days and persisted for up to 841 days (Pickup et al, 2005). MAP cultivation needs up to four months for cultivation with some forms not growing in vitro at all.…”
mentioning
confidence: 99%